Reforma Rimske kurije kot model prenove za vso Cerkev - Saje, Andrej (Bogoslovni vestnik, 2024)
The author uses the historical-analytical method to discuss the significance of Pope Francis’ Apostolic Constitution “Praedicate Evangelium” (2022) and the reform of the Roman Curia for the universal Church. The foundations of the reform are closely linked to the Pope’s vision of the Church, which is reflected in the missionary spirit, the synodal journey of all the baptized, the strengthening of the communion and its participation in the mission of the proclamation of the Gospel. The Roman Curia is called by its very nature to proclaim the Gospel of God’s mercy and to be a model of renewal for the particular Churches. It stimulates the process of growth and pastoral conversion, where a change of mindset and dialogical interpersonal relationships are at the forefront. The Curia is at the service of the Pope, the Bishops and the Bishops’ Conferences. It acts in the name of the Pope and with vicarious power. What stands out in particular is the novelty of the role of the laity, who can now be appointed to the highest leadership positions in the Curia, which shall have consequences for local Churches. In terms of decentralization and subsidiarity, changes are visible in the increased powers of the Bishops’ Conferences. The priority given to evangelization and the new role of the laity are the main emphases that link Pope Francis’ new Apostolic Constitution to the Second Vatican Council (1962–1965) and constitute a new way of putting it into practice.
Keywords: episcopal conference; evangelizacija; evangelization; Frančišek; laiki; laity; Rimska kurija; sinodalna pot; synodal path; škofovska konferenca; the Roman Curia